Patent Dimensions in the Development and Production of COVID-19 Vaccines - Tobias Volpert; Marcel Riepe (Wirtschaftsdienst)
Abstract The process in which COVID-19 vaccines are developed is sequential and continuously accumulating. On the one hand, comprehensive patent protection is a necessary means to promote research and development. It yields additional returns that pay for the occasionally substantial amounts in R&D expenses. On the other hand, patents can be harmful in a sequential development process as they monopolise knowledge that might become a basis for further research. Economic policy cannot resolve this dilemma, but the various dimensions of a patent system can provide a starting point in mitigating a trade-off.